Exploring Fusarium Biocontrol, drought Tolerance, and plant growth promotion by Bacillus strains from Cuban wheat varieties - Alexander Govin-Sanjudo; Marcia M. Rojas Badia; Cédric Jacquard; Qassim Esmaeel (Biological Control)
Members of the Bacillaceae family are recognized for their ability to promote plant growth under drought stress and for their capability to produce bioactive metabolites displaying antagonistic activity against phytopathogenic fungi. In this study, we evaluated the potential of bacterial strains isolated from Cuban wheat accessions to inhibit Fusarium species, tolerate drought stress, and promote the germination of wheat under stress conditions. A total of 150 bacteria were isolated from three Cuban wheat accessions, and 15 isolates were selected based on their elevated antagonistic activity. These strains, belonging to the Bacillaceae family, effectively reduced Fusarium symptoms on wheat leaves. To determine tolerance to drought stress, the isolates were exposed to different concentrations of polyethylene glycol (PEG) −6000, showing tolerance to 20 % PEG-6000. Furthermore, the strains underwent in vitro evaluation for plant growth-promoting (PGP) and lytic enzymes production. Ammonia production, indoleacetic acid, amino cyclopropane carboxylate deaminase, and nitrogen fixation were detected in all bacteria; moreover, each strain produced at least two of the five lytic enzymes tested. The bacterial isolates promoted wheat germination under both drought stress and Fusarium infection; with the highest effects registered for strains TII-10, TII-19, TCG-6 and TMG-6. These findings highlight the potential of these strains as effective agents for the promotion of wheat growth under the dual stresses of Fusarium infection and drought, contributing to more sustainable wheat production.